2004
DOI: 10.1046/j.0041-1132.2003.00518.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of prestorage WBC reduction on the rates of febrile nonhemolytic transfusion reactions to platelet concentrates and RBC

Abstract: Prestorage WBC reduction significantly reduced the rate of FNHTRs to PCs and RBCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
123
0
7

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(142 citation statements)
references
References 20 publications
12
123
0
7
Order By: Relevance
“…12 Leukoreduction of these stored units have been consistently associated with low rates of non-hemolytic febrile transfusion reactions. [13][14][15] Hebert and colleagues evaluated the impact of leukoreduction across 23 Canadian hospitals subsequent to a universal prestorage leukoreduction program. 16 Outcomes evaluated included mortality, infections, fever and antibiotic use among 14,786 patients (6,982 during a period prior to the implementation, and 7,804 after the program's implementation) who received RBC transfusions secondary to cardiac surgery, repair from hip fracture, or during their intensive care unit stay following a surgical intervention or trauma.…”
Section: Discussionmentioning
confidence: 99%
“…12 Leukoreduction of these stored units have been consistently associated with low rates of non-hemolytic febrile transfusion reactions. [13][14][15] Hebert and colleagues evaluated the impact of leukoreduction across 23 Canadian hospitals subsequent to a universal prestorage leukoreduction program. 16 Outcomes evaluated included mortality, infections, fever and antibiotic use among 14,786 patients (6,982 during a period prior to the implementation, and 7,804 after the program's implementation) who received RBC transfusions secondary to cardiac surgery, repair from hip fracture, or during their intensive care unit stay following a surgical intervention or trauma.…”
Section: Discussionmentioning
confidence: 99%
“…Further, FNHTR reaction rates at some institutions where leukoreduction is performed are greater than those at other institutions where it is not. For instance, Patterson et al 2 reported a greater than 10% FNHTR rate for platelet transfusions after the initiation of universal leukoreduction, whereas Yazer et al 4 reported a rate of 0.45% without universal leukoreduction. It therefore seems likely that the discrepancy in reported rates results from the combined effect of multiple variables, potentially including differences in premedication use, patient characteristics, product manufacture, storage time, reporting rates, reaction definitions, and monitoring standards.…”
Section: Incidence and Risk Factors Frequency Of Allergic And Febrilementioning
confidence: 99%
“…Proinflammatory cytokines that accumulate with stored red cell blood products are removed by prestorage leukoreduction, while those that are released by platelet activation may not be removed by leukoreduction. TRALI decreased, but did not disappear, with the implementation of universal leukodepletion in Canada (35). Two reasons account for the decrease in TRALI with leukoreduction: First, the 10% of TRALI cases due to patient antibody against donor leukocytes in the unit of blood would not occur.…”
Section: Cytokinesmentioning
confidence: 99%